(untitled) - Downing, Angela (New York, 1992)
This comprehensive up-to-date descriptive grammar is a complete course for first degree and post-graduate students of Applied Linguistics and English Language. It is also suitable as a background course for literature and discourse studies, since grammatical usage is illustrated with authentic texts, many of them from literary sources.
Keywords: English language,English language; Grammar,Textbooks for foreign speakers; 1950-